Refractory anti-viral resistant CMV retinitis in an immunological nonresponder person living with HIV - Alexandra Serris; Mayda Rahi; Christophe Rioux; Nadhira Fidouh; Veronique Joly; David Boutolleau (International Journal of Infectious Diseases, 2024)
Cytomegalovirus (CMV) retinitis caused by drug-resistant viruses poses a major challenge in immunocompromised patients. We present the case of a patient living with HIV with persistently low CD4+ T cells count despite effective antiretroviral therapy, who experienced multiple episodes of CMV retinitis associated with iterative acquisition of resistance. The failure of ganciclovir and foscarnet treatments led us to implement a combined therapy of intravenous cidofovir, high-dose ganciclovir, and anti-CMV immunoglobulin as well as intravitreal injections of ganciclovir. This triple therapy was successful but resulted in significant myelotoxicity. Furthermore, the relapse of CMV retinitis and/or CMV viremia with each therapeutic de-escalation reflects the high level of immunodeficiency in our patient, despite sustained control of HIV viremia for several months. This case report highlights the need for a particular management of CMV infection in patients living with HIV who are immunological nonresponders.